Weight management barriers and facilitators after breast cancer in Australian women: a national survey - Carolyn Ee; Adele Elizabeth Cave; Dhevaksha Naidoo; Kellie Bilinski; John Boyages (BMC, 2020)
Abstract Background Breast cancer is the most common cancer in women worldwide. Weight gain after breast cancer is associated with poorer health outcomes. The aim of this study was to describe how Australian breast cancer survivors are currently managing their weight. Methods Online cross-sectional survey open to any woman living in Australia who self-identified as having breast cancer, between November 2017 and January 2018. Results We received 309 responses. Most respondents described their diet as good/excellent and reported moderate-high levels of weight self-efficacy. Despite this, the proportion of overweight/obesity increased from 47% at time of diagnosis to 67% at time of survey. More than three quarters of respondents did not receive any advice on weight gain prevention at the time of diagnosis. 39% of women reported being less active after cancer diagnosis, and and few weight loss interventions were perceived to be effective. Facilitators were structured exercise programs, prescribed diets, and accountability to someone else, while commonly cited barriers were lack of motivation/willpower, fatigue, and difficulty maintaining weight. Women who cited fatigue as a barrier were almost twice as likely to be doing low levels of physical activity (PA) or no PA than women who did not cite fatigue as a barrier. Conclusions We report high levels of concern about weight gain after BC and significant gaps in service provision around weight gain prevention and weight management. Women with BC should be provided with support for weight gain prevention in the early survivorship phase, which should include structured PA and dietary changes in combination with behavioural change and social support. Weight gain prevention or weight loss programs should address barriers such as fatigue. More research is required on the effectiveness of diet and exercise interventions in BC survivors, particularly with regard to weight gain prevention.